Challenges for peace education in new democracies - Čorkalo, Dinka (Array, 2000)
The contemporary society faces two parallel processes as a consequence of the end of cold war era. On the one hand, there is process of globalization and cooperation among countries in order to establish rules for peaceful coexistence. In the same time, there are many crisis spots in the world and the collapse of communist regimes in Eastern Europe brought to light suppressed national identities and religious, ethnic and minority issues. In aforementioned countries there is no history and practice of looking at conflicts as a potential for social change, since it was defined as unacceptable and in most of them ethnic and minority issues were forbidden themes translated and viewed as "class struggle". So, the goals of peace education in emerging new democracies are twofold: to accept conflicts as potential for social change and deal with them actively and constructively and to promote right to diversity as common interest in order to enable various national, ethnic and religious groups for living together peacefully. Our point of view is that the tasks of programs for peace education in its narrower meaning are too demanding and almost impossible to accomplish if such programs are isolated from the wider societal level and directed toward only specific groups of people. These groups of people usually include helping professionals of various kind with assumption that they have good chance to disseminate their knowledge and skills to their beneficiaries in everyday work. This is usually very much true and this assumption underlying many peace education programs satisfies common sense logic. But we also deeply believe that the process of establishing peace, tolerance and cooperation as the social norms on community or micro level should be parallel with the same process on the more societal, macro level. This is where peace education starts and ends. In post-conflict new democracies several segments or stages of peace education should be implemented following trucks of two basic educational principles: bottom-up and up-to-bottom approach. Following bottom-up approach we could talk about several stages of peace education process which should be developed. In our opinion these stages should include trauma healing, education for non-violent conflict resolution, education for mutual interdependence, tolerance and respect for diversity, education for social justice and human rights and education for democracy and civil society. On the more macro level, i. e. following up-to-bottom approach, strong institutional support for all stages of peace education should be established. This kind of convergent action could accomplish the final goal of peace education: change of state of mind.